(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The paper discusses classism as an end to justify the actions of indentured workers in the plantations in three geographical regions of the world – Peru, Mauritius and America. In Mauritius, it is seen through the caste system, in America through the prevalence of religious classes and their concomitant support for education, in Peru through the direct and indirect exploitation of Chinese workers. This is in line with the materialist interpretation of history as developed by Marx.